Functional roles of rice glycosyltransferase family GT43 in xylan biosynthesis - Lee, Chanhui (Landes Bioscience, 2014)
Xylan is the major hemicellulose present in both primary and secondary cell walls of rice vegetative tissues. Since xylan is one of the factors contributing to biomass recalcitrance, understanding how xylan is synthesized in rice will potentially provide tools to modify grass biomass composition better suited for biofuel production. Studies of xylan biosynthesis in Arabidopsis have revealed that family GT43 glycosyltransferases, which form 2 functionally nonredundant groups, IRX9/IRX9 homolog and IRX14/IRX14 homolog, are required for xylan backbone elongation. The rice genome harbors 10 genes encoding family GT43 members and it is currently unknown whether they are all involved in xylan biosynthesis. In this report, we performed biochemical analysis of xylan xylosyltransferase activity in rice stem microsomes and investigated the roles of 4 representative rice GT43 members, OsGT43A (LOC_Os05 g03174), OsGT43E (LOC_Os05 g48600), OsGT43H (LOC_Os04 g01280), and OsGT43J (LOC_Os06 g47340), in xylan biosynthesis. OsGT43 proteins were shown to be localized in the Golgi, where xylan biosynthesis occurs. Complementation analysis by expression of OsGT43s in Arabidopsis irx9 and irx14 mutants demonstrated that OsGT43A and OsGT43E but not OsGT43H and OsGT43J were able to rescue the mutant phenotypes conferred by the irx9 mutation, including defective stem mechanical strength, vessel morphology, xylan content, GlcA side chains, xylan chain length, and xylosyltransferase activity. On the other hand, OsGT43J but not OsGT43A, OsGT43E, and OsGT43H restored the defective xylan phenotype in the irx14 mutant. These results indicate that the rice GT43 family evolved to retain the involvement of 2 functionally nonredundant groups, OsGT43A and OsGT43E (IRX9 homologs) vs. OsGT43J (an IRX14 homolog), in xylan backbone biosynthesis.